Perbedaan Usia Pernikahan Anak pada Perempuan Pernah Kawin Usia 15 – 24 Tahun di Perdesaan dan Perkotaan Indonesia - Mona Safitri Fatiah; Yane Tambing; Apriyana Irjayanti (Jurnal Bidan Cerdas, 2023)
Introduction: early marriage in young women will have long-term impacts both in terms of health, social, and psychological children. The aim this study is to see the age difference in child marriage in women who have married aged 15-24 years in rural and urban Indonesia. Method: This study has a cross sectional design conducted for (3 months, with the location of the study being Indonesia. The population of this study was WUS aged 15-24 years who were not married amounting to 38,936 people while the sample in this study was women aged 15-24 years who amounted to 10,691 people. The dependent variable in this study is child marriage with the independent variable is where to live while the confonding variables are age: education, economic status, knowledge of the fertile period, attitudes towards virginity, exposure to information, marriage decision making, dating behavior and first age of dating. The data in this study were analyzed up to a multivariate analysis in the form of logistic regression risk factor model using STATA 14.  Results: The study found women living in rural areas were more likely to marry before age 21 compared to women living in urban areas.  Conclusion: child marriage if not immediately addressed will have an impact on the quality of Human Resources (HR), so a multifactor approach is needed in overcoming the problem.